A Study on Human Resource Practices for Employee#x2019;s Satisfaction and its Impact on Guest Satisfaction Level at Hotels in Greater Noida (Global Journal of Management and Business Research, 2022)
In this study, we will learn about the human resource practices used in the hotel industry to ensure employee satisfaction, as well as the impact on employee performance levels in relation to guest satisfaction. Based on our research, we discovered a variety of practices involved in human resource policy to increase customer satisfaction and the quality of services, as well as the number of steps taken in consideration for improvement and innovation.
Keywords: human resource; performance level; quality of service; human resource policy